Molecular Events of the Crossbridge Cycle Reflected in the Force–Velocity Relationship of Activated Muscle - Seow, Kathryn N.; Seow, Chun Y. (Frontiers in Physiology, 2022)
Muscles convert chemical energy to mechanical work. Mechanical performance of a muscle is often assessed by the muscle’s ability to shorten and generate power over a range of loads or forces, characterized by the force–velocity and force–power relationships. The hyperbolic force–velocity relationship of muscle, for a long time, has been regarded as a pure empirical description of the force–velocity data. Connections between mechanical manifestation in terms of force–velocity properties and the kinetics of the crossbridge cycle have only been established recently. In this review, we describe how the model of Huxley’s crossbridge kinetics can be transformed to the hyperbolic Hill equation, and link the changes in force–velocity properties to molecular events within the crossbridge cycle driven by ATP hydrolysis. This allows us to reinterpret some findings from previous studies on experimental interventions that altered the force–velocity relationship and gain further insight into the molecular mechanisms of muscle contraction under physiological and pathophysiological conditions.